ACCEPTANCE OF STUDENTS TOWARDS E-LEARNING IN MALAY LANGUAGE TEACHING AND LEARNING - Suhaila Ngadiron; Azureen Abd Aziz; Nurien Hidayu Muhamad Rusly, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The development of the information and internet era has transformed traditional learning trends into the form of online versions and has indirectly contributed to the flexible teaching and learning environment. As a result, it seeks to accelerate the teaching and make the learning process more effective. The sample consists of 30 students who take diploma courses from various programs of study. The sample selection was based on random sampling group which seeks to meet the needs of the researcher. For the purpose of this study, a questionnaire was used to collect research information. This survey design was used because of its suitability for reviewing the implementation of e-learning in Malay language teaching and learning. This type of instrument is saving the researchers’ and students’ cost and time. The findings were identified through the acceptance of students towards e-learning in teaching and learning which gave a relatively high overall value of 27. The results of this study showed that students' interest in information technology and the internet as an important intermediate medium today is at a high level. Therefore, this study is expected to be beneficial to the Ministry of Education, lectures, and teachers because they could apply this study as guidance and guidelines in the teaching of Malay language.